Transportation System and Human Needs in a Family - Kadarisman, Muh. (STMT Trisakti, 2015)
Depok City as the main supporting area for the capital city of Jakarta is facing various problems in transportation. Some policies have been made to overcome the problems of transportation, especially traffic jam. Although the system is well developed, it will not succeed as long as it is not sufficiently improved. The aim of this research is to analyze the transportation system and human needs in family in Depok City. The method of research used here is descriptive-qualitative. The results show that to achieve sustainable and environmentally sound development in Depok City, transportation system has an important and strategic position. However, efficient, competitive, cheap transportation services have not been well developed so that it has potential to destruct the environment and cause traffic problems. Such a condition shows the âtrade-offâ the Government of Depok City should face. The enhancement of mobility through providing road infrastructures has supported the economic growth and human beingâs needs in a family. Keyword: transportation system, family need